Novel iodoquinazolinones bearing sulfonamide moiety as potential antioxidants and neuroprotectors - Aiten M. Soliman; Walid M. Ghorab; Dina M. Lotfy; Heba M. Karam; Mostafa M. Ghorab; Laila A. Ramadan (Scientific Reports, 2023)
Abstract In a search for new antioxidants, a set of new iodoquinazolinone derivatives bearing benzenesulfonamide moiety and variable acetamide pharmacophores 5–17 were designed and synthesized. The structures of the synthesized compounds were confirmed based on spectral data. Compounds 5–17 were screened using in vitro assay for their antioxidant potential and acetylcholinesterase (AChE) inhibitory activity. The 2-(6-iodo-4-oxo-3-(4-sulfamoylphenyl)-3,4-dihydroquinazolin-2-ylthio)-N-(pyrazin-2-yl) acetamide 14 was the most active scaffold with potent AChE inhibitory activity. Compound 14 showed relative safety with a median lethal dose of 300 mg/kg (LD50 = 300 mg/kg), in an acute toxicity study. The possible antioxidant and neuroprotective activities of 14 were evaluated in irradiated mice. Compound 14 possessed in vivo AChE inhibitory activity and was able to modify the brain neurotransmitters. It was able to cause mitigation of gamma radiation-induced oxidative stress verified by the decline in Myeloperoxidase (MPO) and increase of glutathione (GSH) levels. Also, 14 restored the alterations in behavioral tests. Molecular docking of 14 was performed inside MPO and AChE active sites and showed the same binding interactions as that of the co-crystallized ligands considering the binding possibilities and energy scores. These findings would support that 14 could be considered a promising antioxidant with a neuromodulatory effect.